Morpho-Syntactic Analysis of Prosecutors’ Resolution - Mangantulao, Gil Vhal; Tandoc, Juanito (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the morpho-syntactic features of prosecutors’ resolutions in the Philippines, focusing on how morphological processes and syntactic structures contribute to legal meaning, interpretation, institutional authority, and accessibility. Guided by Lexical Functional Grammar, the study analyzed lexical entries, word forms, inflection, derivation, phrase and clause organization, grammatical functions, and syntactic dependencies. It employed a qualitative documentary-linguistic design using 16 criminal case resolutions from the Supreme Court E-Library, covering filed and dismissed cases from different Philippine regions. The study did not involve human respondents; each resolution served as a unit of analysis. A qualitative coding scheme was used to identify morphological features, syntactic patterns, and comparative differences, with expert review by a linguist and a prosecutor or lawyer to strengthen reliability. The findings showed that inflection, derivation, compounding, affixation, analytic structures, passive voice, tense, aspect, mood, and allomorphy shaped the formal and technical character of the resolutions. Syntactically, coordination, subordination, transposition, predication, and parallelism organized evidence, legal reasoning, procedural sequence, and judgment. Filed cases emphasized legal action, evidentiary strength, and completion, while dismissed cases emphasized insufficiency, procedural limitation, negation, and distance from agency. The study concluded that morpho-syntactic choices are functional tools in constructing precise, authoritative, and procedurally legitimate legal texts. It recommended integrating morpho-syntactic analysis into legal and linguistic education, simplifying or translating resolutions for non-experts, encouraging language-inclusive legal drafting, conducting linguistic audits, and expanding future research to other legal texts. The study supports SDG 16, SDG 4, SDG 9, and SDG 17 by promoting clearer legal communication, legal literacy, digital accessibility, and interdisciplinary collaboration. Its sustainability impact lies in strengthening institutional transparency, educational development, community legal awareness, and governance-oriented communication.